Teras Samudera Enterprise / Ahmad Tamrin... [et al.] - Tamrin, Ahmad; Asis, Mohd Asrul; Roslin, Mohd Faizul; Mohd Jais, Mohd Hisham; Majauwan, Mohd Sabrie (2012)
Food industries are very much on demand. It is considered as an important thing in everybody's life. Processed food sales in 2004 alone are approximately US$3.2 trillion. In US, consumers spend approximately US$1 trillion annually on food which is 10% of its GDP. There are over 16.5 million people employed in food industry worldwide. Realizing the significance of the fact, we aim to establish a seaweed supplying company named Teras Samudera Enterprise. Seaweeds are popular in Japan, China, Korea, Taiwan, Thailand, Cambodia, Vietnam, Indonesia, Belize, Peru, Chile, Canada, Scandinavia, Ireland, Wales, Philippines, and Scotland. Seaweed are rich in calcium, magnesium and iodine where is the one of healthy foods. According to our research, demand for seaweed is increasing days to days. Plus, there are not many seaweed suppliers in Malaysia, especially here in Sabah. So, it is our aim to play a major part in this kind of product by specializing in seaweed with introducing different flavors to our product. We choose to establish a seaweed supplying company because there is a good future in it as it is able to expand and sustain profit. As a supplier, all we need to do is having the right place, which brings benefits to us. Our proposed company will be located at Tuaran. The location chosen is suitable for us because it has many retail stores around that will be our potential customers and users of our services. It is also close to the main road making it easier for distributing activities.